2002
DOI: 10.1002/ijc.10434
|View full text |Cite
|
Sign up to set email alerts
|

Novel camptothecin derivative BNP1350 in experimental human ovarian cancer: Determination of efficacy and possible mechanisms of resistance

Abstract: The novel camptothecin derivative BNP1350 (7-[2-trimethylsilyl)ethyl]-20(S)-camptothecin), also known as Karenitecin, has been developed for superior oral bioavailability and increased lactone stability. In our study, we describe the antiproliferative effects of BNP1350, SN-38 and topotecan in 4 human ovarian cancer cell lines. BNP1350 was found to be slightly more potent than SN-38 (p<0.01) and was considerably more potent than topotecan (p<0.01). We extended these studies to well-established human ovarian ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…33 Another camptothecin analogue, karenitecin (BNP1350), is not an ABCG2 substrate. 34 Other studies have identified modifications of the camptothecin parent structure which abolish ABCG2-mediated efflux. 35 9-Nitrocamptothecin has intermediate affinity for…”
Section: Topoisomerase Inhibitiorsmentioning
confidence: 99%
“…33 Another camptothecin analogue, karenitecin (BNP1350), is not an ABCG2 substrate. 34 Other studies have identified modifications of the camptothecin parent structure which abolish ABCG2-mediated efflux. 35 9-Nitrocamptothecin has intermediate affinity for…”
Section: Topoisomerase Inhibitiorsmentioning
confidence: 99%
“…Cancer cells that express BCRP are not resistant to camptothecin itself, or to the camptothecin analogs BNP1350, DX8951f, or NX211 (Ishii et al, 2000;Maliepaard et al, 2001b;Van Hattum et al, 2001;Van Hattum et al, 2002). Studies of SN-38-and irinotecan-resistant PC-6 sublines, which overexpress BCRP, also demonstrated that these cells were not resistant to the clinically promising water-soluble camptothecin analog DX-8951f (Ishii et al, 2000).…”
Section: Resistance To Topoisomerase I Inhibitorsmentioning
confidence: 99%
“…Kruijtzer et al (2002) also demonstrated evidence for decreased biliary and renal excretion of topotecan by GF120918 by showing that the drug reduces plasma clearance of topotecan administered intravenously. Newer camptothecin derivatives such as BNP1350, likely owe their superior oral bioavailability to the fact that they are poor substrates for BCRP (Van Hattum et al, 2002). …”
Section: Bcrp Effects On Drug Bioavailability Pharmacokineticsmentioning
confidence: 99%
“…Selection with mitoxantrone [68], topotecan [69,70] or SN-38 [71] results in ABCG2 overexpression as does selection with flavopiridol [72]. Even selection with DX-8951f or BNP-1350, camptothecins that are relatively poor ABCG2 substrates, results in ABCG2 upregulation [73,74]. Indolocarbazole topoisomerase I inhibitors J-107088 and NB-506 [75] have been shown to be transported by ABCG2, as have the tyrosine kinase inhibitors CI1033 [76], gefitinib [77], and imatinib [78].…”
Section: Substrates Of Abcg2mentioning
confidence: 99%